Study on debt maturity of Portuguese SMEs 2009-2011 - Costa, Sérgio Guimarães Monteiro da (2013)
The purpose of this empirical work is to understand the reasoning behind debt maturity choices from Portuguese SMEs and to see if those choices are made based on the existent debt maturity theories proposed by the finance literature. We consider an important period for the Portuguese economy where the country was starting to feel the effects of the 2008 financial crisis and where companies, especially small ones, had to make smart long time decisions about their debt levels and maturities in order to survive future tough austerity policies. With a sample of 2,000 Portuguese SMEs for the time period between 2009 and 2011, using panel data methodology, we run two sample mean comparison t-tests as well as fixed effects model regression in order to study the debt maturity determinants within SMEs. An increasing trend was found on average debt maturity during the three years on analysis. Our study showed partially consistent results with Diamond´s (1991) theory where intermediate quality firms choose to issue more long term debt while high quality firms tend to issue more short term debt. Smaller firms (those more affected by asymmetric information) tend to use debt of shorter maturities. Furthermore, we find evidence supporting the clientele argument where firms affected by higher tax rates have longer debt maturities. Finally, firms with more growth opportunities are using more short term debt.